HUBUNGAN KARAKTERISTIK SOSIO-DEMOGRAFI ORANG TUA DENGAN KEJADIAN PERNIKAHAN USIA DINI PADA WUS KECAMATAN TEMBALANG KOTA SEMARANG TAHUN 2018 - Sarah Ayu Tifana; Djoko Nugroho; Yudhy Nugroho; Dharminto Dharminto (Jurnal Kesehatan Masyarakat, 2019)
Early marriage is a marriage conducted by women at the age before 21 years. Early marriage can have negative effects on health. Parents' socio-demographic factors such as education level, employment status, and the number of children can cause early marriage. In 2017, Tembalang District had the highest early marriage incidence in Semarang. 97 women were conducting early marriages in Tembalang District in 2018, Sendangguwo (18 WUS) and Meteseh (18 WUS) Subdistricts had the highest incidence of early marriage. The purpose of this study is to analyze the relationship of parents' socio-demographic characteristics with the incidence of early marriage in Sendangguwo and Meteseh Sub-District, Tembalang District, Semarang in 2018. The type of this research is explanatory research using a cross-sectional design study. The population is all women who got married in 2018 with a total sample of 71 women. The sampling technique used is proportional random sampling. The scale in this study is a nominal scale using the contingency coefficient statistical test. The results showed that the highest percentage of parents have low education levels (62%), unemployed (63.4%), the number of children <5 person (80.3%), and women who did not marry early (71.8%). The bivariate test results in this study indicate that there is a weak relationship between the level of education of parents (p-value=0,026, C=0,285), parents occupation status (p-value=0,036, C=0,271), and there isn't any relationship between the number of children (p-value 0.571) with the incidence of early marriage in Sendangguwo and Meteseh Sub-District, Tembalang District, Semarang in 2018. Socialization and counseling are needed regarding early marriage, socialization and distribution of leaflets regarding reproductive health, distribution of posters and leaflets about 12-year compulsory education and Smart Indonesian Program.